2018
DOI: 10.3390/app8081277
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature, pH, and Reaction Duration on Microbially Induced Calcite Precipitation

Abstract: In this study, the amount of calcite precipitate resulting from microbially induced calcite precipitation (MICP) was estimated in order to determine the optimal conditions for precipitation. Two microbial species (Staphylococcus saprophyticus and Sporosarcina pasteurii) were tested by varying certain parameters such as (1) initial potential of hydrogen (pH) of urea-CaCl2 medium, (2) temperature during precipitation, and (3) the reaction duration. The pH values used for testing were 6, 7, 8, 9, and 10, the temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 40 publications
0
50
0
1
Order By: Relevance
“…to group the samples according to their similarity. 33 The complete linkage algorithm and city block (Manhattan) distances were used to explain the differences in the temperature growth profile of the isolates, which were grouped in three clusters (Fig. 1).…”
Section: Cluster Analysismentioning
confidence: 99%
“…to group the samples according to their similarity. 33 The complete linkage algorithm and city block (Manhattan) distances were used to explain the differences in the temperature growth profile of the isolates, which were grouped in three clusters (Fig. 1).…”
Section: Cluster Analysismentioning
confidence: 99%
“…The influence of pH on MICP is indisputably important because it affects microbial activity, bacterial growth, urease activity, and CaCO 3 precipitation [65]. Decomposition of urea by urease that releases NH 3 (g) and CO 2 (g) and the dissolution of NH 3 (g) in the urea-CaCl 2 leads to a variation of pH during ureolysis process [85].…”
Section: Ph Measurementmentioning
confidence: 99%
“…pH and temperature pH and temperature have a direct bearing on the growth and urease activity of the bacteria. S. pasteurii is sensitive to pH and temperature during the cementation process as some studies have shown (Kim et al, 2018;Sun et al, 2019). pH and temperature also have impacts on the equilibria of dissolution and precipitation during MICP process.…”
Section: Urease and Its Activitymentioning
confidence: 99%
“…During MICP process, Stocks-Fischer et al (1999) determined that MICP starts at pH ¼ 8.3 and its rate increases up to pH 9. Kim et al (2018) studied the effect of the pH (in the range of 6-10) of an urea-CaCl 2 solution and found that pH ¼ 7 was the optimal condition for biocementation.…”
Section: Urease and Its Activitymentioning
confidence: 99%
See 1 more Smart Citation